Analisis Pembelajaran Jarak Jauh Pada Mata Pelajaran Pendidikan Fiqih di SMK Muhammadiyah Semim (Equilibrium: Jurnal Pendidikan, 2022)
This study discusses the analysis of distance learning in fiqh education subjects for class XI at SMK Muhammadiyah Semin.  The purpose of this study was to determine the effectiveness of distance learning in fiqh education subjects for class XI at SMK Muhammadiyah Semin. The research method used is descriptive analysis method with qualitative approach. Data collection techniques are observation, interviews and documentation, research subjects are principals, ISMUBA teachers, curriculum fields and students. Analysis of data reduction, display, verificationDistance learning in fiqh education subjects for class XI has compatibility of learning devices with the implementation of learning as much as 83.4% The learning achievement of fiqh education for class XI is quite good with 15% getting very good scores (A), 51% getting good grades (B) and 34% getting enough grades (C), and all student scores have met the minimum score or KKM
Keywords: PJJ; Fiqh Education